2015
DOI: 10.1002/wcc.376
|View full text |Cite
|
Sign up to set email alerts
|

Community‐based adaptation research in the Canadian Arctic

Abstract: Community‐based adaptation (CBA) has emerged over the last decade as an approach to empowering communities to plan for and cope with the impacts of climate change. While such approaches have been widely advocated, few have critically examined the tensions and challenges that CBA brings. Responding to this gap, this article critically examines the use of CBA approaches with Inuit communities in Canada. We suggest that CBA holds significant promise to make adaptation research more democratic and responsive to lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 114 publications
(215 reference statements)
0
52
0
Order By: Relevance
“…[11][12][13][14][15][16] This literature was heavily influenced by political ecology approaches [17][18][19][20] that argued for greater consideration of politics in the environmentdevelopment field at this time. These critical debates provide a foundation for newer approaches, for example, community-based adaptation (CBA), [21][22][23] an approach that aims to empower communities to plan for and cope with the impacts of climate change. However, calls for further critical study of CBAs to examine the tensions and challenges that it brings illustrate the challenge of a more critical approach filtering into policy and practice.…”
Section: Critical Community and Participation In The Global Southmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16] This literature was heavily influenced by political ecology approaches [17][18][19][20] that argued for greater consideration of politics in the environmentdevelopment field at this time. These critical debates provide a foundation for newer approaches, for example, community-based adaptation (CBA), [21][22][23] an approach that aims to empower communities to plan for and cope with the impacts of climate change. However, calls for further critical study of CBAs to examine the tensions and challenges that it brings illustrate the challenge of a more critical approach filtering into policy and practice.…”
Section: Critical Community and Participation In The Global Southmentioning
confidence: 99%
“…However, calls for further critical study of CBAs to examine the tensions and challenges that it brings illustrate the challenge of a more critical approach filtering into policy and practice. 22 While much communities and climate change focus in the global north has been given to mitigation, in the global south, where significant negative impacts on development are expected, attention has focused on adaptation through CBA. With the proliferation of payment for ecosystem services programs in the global south and moves from piloting to implementing REDD+ (climate change mitigation), communities will remain central.…”
Section: Critical Community and Participation In The Global Southmentioning
confidence: 99%
“…Research on collaborative, or participatory, research processes involving scientists, stakeholders, and policy or decision makers has shown that participants tend to trust scientific information more [57] and are more likely to use it to inform decisions when they collaborated in the process of developing the knowledge [58,59]. However, we know from research like Beierle [60], Nadasdy [61], Rowe and Frewer [62], Stern and Fireberg [63], and Ford et al [64], among others, that not all collaborative processes are equal. The ways in which scientists engage with other parties-the processes they use-matters to the outcomes.…”
Section: Collaborative Approaches To Natural Resource Managementmentioning
confidence: 99%
“…Ford et al unpack some of the challenges and potential issues with even the most well-intentioned participatory research work focusing on CBA [64]. Based on their experiences with CBA approach to climate change impacts, they note that researchers cannot assume that research has a positive role to play in a community, just because it uses participatory processes; sometimes-new research is not the answer to a community's needs.…”
Section: Collaborative Approaches To Natural Resource Managementmentioning
confidence: 99%
“…Climate adaptation planning is a key response to manage vulnerability and uncertainty from the potential impacts of climate change (Adger & Barnett, 2009;Farbotko & Lazrus, 2012;O'Brien and Wolf, 2010). Climate adaptation planning is also conceptualised as a socially and politically mediated process that draws social groups and institutions into contested decisions about trade-offs and multiple responses to observed or expected impacts of climate change, particularly in the context of diverse interpretations of vulnerability across societies (Adger & Barnett, 2009;Ford et al, 2016;International Panel on Climate Change, 2014). For Indigenous peoples in settler societies, planning is increasingly becoming a key "site" for the assertion of their rights and interests in climate adaptation and other planning arenas (Porter, 2017).…”
Section: Introductionmentioning
confidence: 99%